Implementing cognitive remediation and social cognitive interaction training into standard psychosis care - Frances Dark (BMC Health Services Research, 2018)
Abstract Background To evaluate the planned implementation of group based Cognitive Remediation therapy (CR) and Social Cognitive Interaction Training (SCIT) into routine psychosis care in a mental health service in Australia. Method The study was conducted over 3 years in a mental health service in a metropolitan city in Australia. Participants were 22 program facilitators and 128 patients attending the programs. Implementation outcomes were assessed using administrative data, staff surveys and program audits. Results There was fidelity to the particular therapies at a program level. Programs were assessed as being feasible within the study setting with each hospital district developing a capacity to run CR and SCIT. The establishment of new programs improved the reach, but waiting lists indicate a need to expand capacity. There was a relatively high dropout and several factors impacted on completion of the programs - notably, acute exacerbation of psychosis. Once initiated the therapies were acceptable with no-one ceasing SCIT due to loss of interest and only 10% of participants ceasing CR due to loss of interest. Annual audits of programs found programs established were maintained and facilitators were retained. Conclusion SCIT and CR programs were successfully implemented in three hospital districts. Several factors impeded participants receiving the recommended “dose” of the programs. The maintenance of the programs in the short term is encouraging in regards to organisational fit. Dissemination of cognitive rehabilitation programs to a service population takes planning. An implementation plan is essential for guiding development and maintenance of programs. These therapies are best suited to people in a stable phase of illness. Service user co-production is recommended to improve recruitment in future studies.